Plasmids: Tiny pieces with high efficacy (Review) - Osamah Faisal Kokaz; Duaa abd Alabbas Muhammad; Mohammed Mudhafar Alkhuzaie (Journal of Medical Genetics and Clinical Biology, 2024)
Plasmids are of paramount importance in the field of bacterial ecology and evolution due to their facilitation of the horizontal transfer of accessory genes (HGT). It has become evident that, apart from their evolutionary role, plasmids also have the ability to influence the expression of various bacterial traits. Approximately 25% of the plasmids contain the necessary functions to autonomously undergo conjugation, while the remaining plasmids can be mobilized through conjugation at a later time. Given their potential significance, this review centers on the role of these minuscule sequences of nucleotides in various biological activities